2019
DOI: 10.30802/aalas-jaalas-18-000076
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Sustained-release Compared with Conventional Formulations of Meloxicam in Sheep (Ovis aries)

Abstract: Sustained-release (SR) drugs refine current analgesic regimens by alleviating the need for multiple sessions of handling and restraint and by reducing the local tissue irritation that can occur due to repeated injections. Although a variety of SR drugs are already used in lab animal medicine, no studies exist that evaluate the suitability of an SR NSAID in sheep. This study used HPLC-MS to measure the plasma concentrations of 2 formulations of meloxicam-conventional and SRMafter subcutaneous administration in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The T max of the SRMF in this study (10 h) was twice that of the CMF reported by a previous study (5 h), demonstrating that the rate of absorption of the SRMF in this study was slower [12]. Similarly, another study using a SRMF was found to have a T max of 6.70 h in sheep, which is longer than that for CMF but less than the T max in this study [17].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The T max of the SRMF in this study (10 h) was twice that of the CMF reported by a previous study (5 h), demonstrating that the rate of absorption of the SRMF in this study was slower [12]. Similarly, another study using a SRMF was found to have a T max of 6.70 h in sheep, which is longer than that for CMF but less than the T max in this study [17].…”
Section: Discussionsupporting
confidence: 54%
“…The plasma concentrations of the SRMF used in this study provided an extended t 1/2 of 31.40 h comparative to the CMF t 1/2 of 14.28 h, when both were administered at 2 mg/kg via SC injection [ 12 ]. In a recent study in sheep, it was found that the t 1/2 for a SC injection of SRMF (10 mg/mL, Zoopharm, Fort Collins, CO, USA) administered at 1.5 mg/kg was 15.2 h [ 17 ]. This difference may be due to a difference in dose rate and/or due to differences in the formulation and/or individual animal differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue depletion studies are necessary to create a robust, scientifically based WDI following extra-label use of any medications, however published tissue depletion studies are limited compared to live animal pharmacokinetic studies that rely mostly on serum or plasma concentration data. Current estimated pharmacokinetic parameters for sheep administered meloxicam were derived from plasma concentrations and are limited to a single oral, subcutaneous (SC) or intramuscular (IM) dose or multiple SC doses [1,2,6,8,9]. Single oral dose data has limited clinical application since many conditions requiring treatment with anti-inflammatory pain medication do not resolve in a single day, and multiday therapy is commonly warranted and prescribed by veterinarians.…”
Section: Introductionmentioning
confidence: 99%
“…Both formulations were found in the studies reviewed. The use of 1.0 mg/kg dose of meloxicam was frequently used across all studies except for two studies which used a lower than recommended dose of 0.5 mg/kg [31,32]. An analgesic effect was not recorded when meloxicam was given at this lower dose, and it is unclear whether this lower dose would offer effective pain relief.…”
Section: Nsaidsmentioning
confidence: 99%